2017
DOI: 10.1037/tra0000225
|View full text |Cite
|
Sign up to set email alerts
|

Identity adjustment among Afghanistan and Iraq war veterans with reintegration difficulty.

Abstract: Identity adjustment is a critical yet understudied aspect of veteran reintegration into community life following combat deployment. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 33 publications
5
72
0
Order By: Relevance
“…Finding an alternative narrative is about finding one's group: one's subculture (see also McLean, 2015). Indeed, studies on a broad array of topics-from veterans returning to civilian life (Orazem et al, 2016) to working-class college students navigating home and school lives (Azmitia, Syed, & Radmacher, 2013)-show that the tension in navigating between various groups can be a serious source of identity strain. Indeed, recent work has shown that master narratives are partly maintained via social interaction, such that the desire to connect with others trumps the desire to air challenges to the status quo .…”
Section: Alternative Narrative Construction Is Socialmentioning
confidence: 99%
“…Finding an alternative narrative is about finding one's group: one's subculture (see also McLean, 2015). Indeed, studies on a broad array of topics-from veterans returning to civilian life (Orazem et al, 2016) to working-class college students navigating home and school lives (Azmitia, Syed, & Radmacher, 2013)-show that the tension in navigating between various groups can be a serious source of identity strain. Indeed, recent work has shown that master narratives are partly maintained via social interaction, such that the desire to connect with others trumps the desire to air challenges to the status quo .…”
Section: Alternative Narrative Construction Is Socialmentioning
confidence: 99%
“…Finding an alternative narrative is about finding one's group -one's sub-culture (see also McLean, 2015). Indeed, studies on a broad array of topicsfrom veterans returning to civilian life (Orazem et al, 2016), to working class college students navigating home and school lives (Azmitia, Syed, & Radmacher, 2013) -show that the tension between in navigating various group can be a serious source of identity strain. Indeed, recent work has shown that master narratives are partly maintained via social interaction, such that the desire to connect with others trumps the desire to air challenges to the status quo .…”
Section: Master Narrative Deviations 39mentioning
confidence: 99%
“…Veterans frequently face a sense of disconnectedness in their social lives (i.e., loneliness, social isolation) and personal lives (i.e., self-connectedness -lack of purpose or goals) when they leave the military. [1][2][3][4] This lack of connectedness, both social and self, has been established as a risk factor for suicidal behaviors. 5 However, surprisingly few interventions, especially suicide prevention efforts, seek to improve veterans' overall connectedness or focus on the reintegration experience specifically.…”
Section: Introductionmentioning
confidence: 99%